(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2026)
Objective: To determine the incidence and levels of total, direct, and indirect serum bilirubin, and to identify the clinical and demographic determinants of neonatal hyperbilirubinemia among jaundiced neonates admitted to a tertiary care hospital in district Swat, Khyber Pakhtunkhwa, Pakistan. Methodology: This descriptive cross-sectional study was conducted in the NICU of Saidu Group of Teaching Hospitals, Swat, over six months, enrolling 160 neonates with jaundice. Neonates without jaundice and those not admitted at SGTH were excluded. Data on sociodemographic and clinical variables, along with serum bilirubin levels, were collected via a structured questionnaire. Analysis was performed using SPSS version 22, summarizing categorical variables as frequencies and percentages, with associations tested using the chi-square test (p<0.05 significant). Results: Of 160 neonates studied, 25% were preterm, 75% term, and 59.4% male. High total bilirubin levels (13–18 mg/dL) were found in 50.6%, with severe cases (>18 mg/dL) at 27.5%. Direct bilirubin was moderately elevated in 53.1%, while 52.5% had severely raised indirect bilirubin (>13 mg/dL). Significant associations with total bilirubin included age at admission and mode of delivery (p<0.001), as well as breastfeeding (p=0.006 for total and p=0.029 for indirect bilirubin). Key determinants of hyperbilirubinemia included ABO incompatibility (18.1%), Rh incompatibility (13.8%), neonatal sepsis (15.6%), and breastfeeding (49.4%). Home delivery correlated with cephalohematoma, meconium aspiration syndrome, and neonatal mortality (p<0.05). Overall mortality due to hyperbilirubinemia was 5.6%, significantly linked to higher bilirubin levels (p=0.025 for total and p=0.014 for direct). Conclusion: Neonatal hyperbilirubinemia remains a substantial burden in this population, with late presentation, non-facility delivery, prolonged/excessive breastfeeding, and blood-group incompatibilities emerging as the principal determinants of severe bilirubin elevation and mortality.